At-Thibaq Min Al-Ayat Al-Qur’aniyah Wal Istifadat Minha Fi Ta’limi Al-Lughah Al-Arabiyah - Ibrahim, Rosmala; Kholiq Hasan, Moh. Abdul (Lembaga Penelitian dan Pengabdian Masyarakat, Sekolah Tinggi Ilmu Bahasa Arab Ar Raayah, 2023)
إن تعليم اللغة العربية هو إيصال المعلم على اللغة العربية ومعرفتها إلى أذهان التلاميذ بطريقة قويمة لكي يحصلوا على المهارات اللغوية الأربع المنشودة. ومن المعلوم أن علوم اللغة العربية عديدة منها علم البلاغة التي يبحث فيه عن المحسنات الألفاظ منها أسلوب الطباق وهو الجمع بين لفظين متقابلين في المعنى ويعبر جمال الكلمة في المعنى فلذلك وجد كثيرا من ألفاظه في الآيات القرآنية. مهما درسوا هذا الموضوع في علم البلاغة، يستطيع المعلم أن يستفيده على شكل أو طرق متنوعة في هيئة جديدة لارتقاء مستوى لغة متعلم خاصة في استعاب المفردات بفهم أساليب الطباق. لأجل ذلك إن هذه الدراسة تهدف إلى استفادة الطباق من الآيات القرآنية في تعليم اللغة العربية. وتسلك هذه الدراسة منهج الوصفي التحليلي، وذلك بتتبع أساليب الطباق من الآيات القرآننية وبيان طرق تعليمها على هيئة جديدة. أثبتبت الدراسة من خلال نتائجها على وجود أساليب الطباق في الآيات القرآنية و قد تم عرضها مع بيان أنواع وألفظها. وكذلك أثبتت إمكانية الاستفادة منها استفادة جيدة في تعليم اللغة العربية. وذلك بأن يقوم المعلم مبنيا هذه الدراسة بواسطة الحوار والنص ليفهم المتعلم المفردات المأخوذ من ألفاظ الطباق ويقدر على إنشائها في الجملة المفيدة مع إعطائم التدريبات. Teaching the Arabic language is the teacher's introduction to the Arabic language and its knowledge in the minds of the students in a correct way in order for them to obtain the four desired language skills. It is well known that the sciences of the Arabic language are many, including the science of rhetoric, in which it searches for fine expressions, including the counterpoint method, which is the combination of two opposite words in meaning and expresses the beauty of the word in meaning, so many of its words were found in the Quranic verses. No matter how much they study this subject in the science of rhetoric, the teacher can benefit from it in a variety of forms or methods in a new form to raise the level of a learner's language, especially in absorbing vocabulary by understanding counterpoint styles. For this reason, this study aims to benefit from the Qur'anic verses in teaching the Arabic language. This study adopts the descriptive analytical approach, by following the counterpoint methods of the Quranic verses and explaining the methods of teaching them in a new form. The study proved, through its results, the existence of counterpoint styles in the Quranic verses, and they were presented with an indication of their types and pronunciations. The possibility of benefiting from it has also proven to be a good benefit in teaching the Arabic language. This is so that the teacher builds this study through dialogue and text so that the learner understands the vocabulary taken from the counterpoints and is able to create them in the useful sentence while giving them exercises.